EFEK JUS BATANG BROTOWALI (Tinaspora crispa L. Miers) TERHADAP GAMBARAN GLUKOSA DARAH DAN HISTOPATOLOGIK PANKREAS TIKUS WISTAR YANG DIINDUKSI ALOKSAN - , M.ZIADY RIFKI NURABIDI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia. Synthetic drugs are not effective enough, it has side effect and need a cost quite expensive. One of the alternative medicines used to treat diabetes mellitus is a Brotowali (Tinaspora crispa L. Miers). The aim of this research is to understand the effect of Brotowali stem juice to blood glucose and histopathological pancreas of diabetic rats Twenty five rats of Wistar strain were divided into five group. Group I, II, III, IV were injected by Alloxan tetrahydrat three times at a dose of 150 mg/kg BW/IP exception of group V, which was a negative control. Group I treated brotowali stem juice 18 mg/200 g Bw /day orally. Group II and III treated brotowali stem juice 9 mg/ 200 g BW/ day orally. Group IV as a positive control was given 1 mL of aquades. Group V without injection of Alloxan was given Brotowali stem juice dose 9 mg/200 g Bw/day as a negative control. Measurement of blood glucose levels was done at 0th, 6th, 12th, 18th, 25th, 28th days. At the end of the study (at 29th day) all rats were killed, and histology of the pancreas were taken for examination. The result of blood glucose level (mg/dl) was analyzed by one way ANOVA used SPSS methode at significance level of 5%, Multivariate test, Duncan test, LSD test and histopathology of pancreas descriptively. The result of the study showed an increase blood glucose level of control positif but not significant (p>0.05) and significant decrease of blood glucose on negatif and treatment control (p<0.05). There is no difference between brotowali stem juice dose 9 mg/200 g and 18 mg /200 g, both of dose can decrease blood glucose level significantly (p<0.05). Histhopatological images, the positive control (group IV) showed fewer number of Langerhans cells, hidrofik degeneration, vacuolization in the cytoplasm, cell necrosis. In the negative control group (group V) and treatment group (group I and II) looks lighter than the positive control group (group IV). The conclusion of the study that Brotowali stem juice can decrease blood glucose levels significantly (p<0.05). Results of histopathological pancreas supports blood glucose levels above. Keywords: diabetes mellitus, Brotowali stem juice, blood glucose, Alloxan tetrahydrat, histopathology of pancreas